2012
DOI: 10.1097/mao.0b013e3182544e73
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Taste Function in Patients With Middle Ear Disease

Abstract: Our findings suggest that the filter paper disk scores of all taste qualities (sweet, salty, sour, and bitter tastes) are not deteriorated preoperatively during chronic inflammation in the middle ear and that taste function is affected most in patients with pars tensa retraction-type cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…According to the reports concerning the gustatory function measured by electrogustometry (EGM) in patients with chronic otitis media, gustatory dysfunction occurred, but differences existed among investigations. [5][6][7][8] If the gustatory function deteriorates in combination with morphological changes of the CTN in patients with chronic otitis media, a question arises as to whether or not gustatory end organs on the surface of the tongue, especially taste buds in fungiform papillae (FP), are also damaged. To date, morphological observation of fungiform taste buds in patients with chronic otitis media has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reports concerning the gustatory function measured by electrogustometry (EGM) in patients with chronic otitis media, gustatory dysfunction occurred, but differences existed among investigations. [5][6][7][8] If the gustatory function deteriorates in combination with morphological changes of the CTN in patients with chronic otitis media, a question arises as to whether or not gustatory end organs on the surface of the tongue, especially taste buds in fungiform papillae (FP), are also damaged. To date, morphological observation of fungiform taste buds in patients with chronic otitis media has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In 10 studies, no clear report was available regarding CTN preservation or iatrogenic lesion. Outcome of these studies did not evaluate CTN status . Seven studies were excluded due to a lack of preoperative diagnosis for ear surgery because it was unclear if patients with inflammatory disease were included.…”
Section: Resultsmentioning
confidence: 99%
“…After title and abstract screening, 58 articles were assessed for eligibility in full text. In total, 30 studies reported on the gustatory function after ear surgery . In 10 studies, no clear report was available regarding CTN preservation or iatrogenic lesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed histopathologic changes of the CTN caused by inflammation, such as thickening of perineural and epineural connective tissue, vacuolar degeneration of Schwann cells, and proliferation of fibroblasts in the endoneurium . The damage to CTN function already may have occurred by inflammation in patients with inflammatory middle ear disease before the surgery . Such patients are unlikely to notice a change of taste sensation in the event of nerve injury during ear surgery.…”
Section: Discussionmentioning
confidence: 97%